Programmatic implications of unmet need for contraception among men and young married women in northern Nigeria - Sinai I; Nyenwa J; Oguntunde O (Dove Medical Press, 2018)
Irit Sinai,1 Jabulani Nyenwa,2,3 Olugbenga Oguntunde2,4 1Palladium, Washington, DC, USA; 2UKAid/Nigeria MNCH2 Programme, Kano, Nigeria; 3Palladium, London, UK; 4Palladium, Abuja, Nigeria Purpose: The study was designed to provide programmatic recommendations for interventions to increase contraceptive prevalence in northern Nigeria. Family-planning use in North-East and North-West regions of Nigeria has remained very low, despite years of domestic and donor investments. We examine respondents’ perceptions of their own need for contraception and specifically focus on young women because of their higher risk for maternal mortality.Methods: In this cross-sectional study, we interviewed 1,624 married women younger than 25 years and 1,627 men married to women younger than 25 years, in Kaduna and Katsina states in northern Nigeria. We classified respondents into five categories: 1) having no real need for contraception, 2) perceiving no need for contraception, despite physical or behavioral need, 3) having met need by using a modern contraceptive method, 4) perceiving met need by employing traditional practices, and 5) having unmet need for contraception.Results: Half of female respondents had no need for contraception because they were either pregnant or desiring a pregnancy at the time of the survey. A quarter of female and male respondents were not using contraception because of their religious beliefs. Less than 2% of respondents had unmet need because of lack of availability or access, or due to poor quality of care. Men had more positive views of family planning than women.Conclusion: Our findings suggest that young women in northern Nigeria would benefit from a programmatic approach that targets men, utilizes religious leaders, and addresses the prevalent religious and sociocultural norms that present barriers to contraceptive use. Such interventions have the potential to increase contraceptive prevalence more substantially, but the literature on these types of interventions in northern Nigeria is scarce. Therefore, more research is needed to identify and document what approaches work or do not work to increase contraceptive use in northern Nigeria. Keywords: family planning, unmet need, adolescents, northern Nigeria, religious norms, social norms